Pengaruh Elemen Fraud Diamond Terhadap Potensi Kecurangan Pengelolaan Dana Desa - Rohanisa, Dina; Bhilawa, Loggar (Universitas Gorontalo, 2022)
This research aims to examine the effect of pressure, opportunity, rationalization, and capability on the potential for fraud in the management of village funds in Cilacap Regency. The data used are primary data sources by distributing questionnaires to village heads and village officials in Cilacap Regency. The data analysis model used is multiple linear regression. The results of the study show that pressure, opportunity, rationalization, and capability have a significant positive effect on the potential of village fund fraud.